Satellite images in the new Atlas «Russian Arctic» - V. I. Kravtsova; E. I. Pizhankova; A. I. Kizyakov; A. V. Gavrilov (Лëд и снег, 2019)
The increasing interest in the Arctic promotes appearance of new cartographic products to provide information for the primary tasks of this region development. So, several atlases of the Arctic have been already published. At the initiative and with the financial support from the oil and gas industry, a new Atlas «Russian Arctic» is being prepared for publication, in which considerable attention is given to the environmental aspects of the development of the North with account for conditions of changing climate. Unlike previous atlases, this Atlas contains thematic sets of satellite images reflecting changes in the natural environment, in particular, different types of natural ice under conditions of warming. The space part of the Atlas developed by the authors of this article covers a number of subjects. Thus, the decrease in the area of sea ice is illustrated by the materials of shooting from the space of the Northern polar cap for the period of the largest reduction in the area. Images made in different time fix retreating of the shores, composed of underground ice, being the result of the processes of thermal abrasion, thermal erosion and thermal denudation. Complicated ice conditions of navigation in the Ob Bay and characteristics of the Arctic rivers mouths are presented by pictures of tidal estuaries of the rivers Mezen and Kuloi. Images of ice jams at the mouth of the Northern Dvina River and materials of space monitoring of measures for liquidation of them are also given in the Atlas. Special attention is given to forms of permafrost relief, which are well displayed in high-resolution images. They show a polygonal micro-relief of different types and stages of development of them, as well as frost mounds, dales, and thermo-erosion forms. Formation of aufeises (naleds), thermokarst lakes, and craters of gas outbursts is also shown. The wildlife of the Arctic is represented in the Atlas as well. The pictures present a visual image of different types of tundra. The influence of warming on vegetation development is well reflected in the photo map of the dynamics of the vegetation index for 2000-2009, showing the growth of phytomass in the European North. The Atlas contains unique materials of satellite monitoring of Arctic mammals - walruses and seals. The impact of using mineral resources on the vulnerable nature of the Arctic is shown in the Khibiny region. Prominent examples of the vegetation degradation in the areas of Norilsk and Monchegorsk cities are given, where technogenic wastelands have been formed under the sulfuric acid fumes of the copper-nickel plants.